Postbiotic supplementation stabilizes gingivitis and improves zootechnical performance of Brangus heifers in an extensive grazing system - Saraiva, Júlia Rebecca; de Almeida, Jonatas Campos; Manzano, Ricardo Pereira; Beda, Sabrina Pereira Bomfim; Riggio, Marcello Pasquale; Dutra, Iveraldo Santos; Borsanelli, Ana Carolina (Frontiers in Veterinary Science, 2026)
Gingivitis represents an early and reversible stage of periodontal disease in cattle and may influence animal welfare and productivity. Controlling this condition in grazing systems remains challenging, and nutritional strategies could represent a sustainable approach to oral health management. This study evaluated the effect of three dietary supplements on the occurrence of gingivitis in incisor teeth and on weight performance of 150 crossbred Brangus beef heifers maintained on Brachiaria pasture for a period of 4 months. The animals were allocated into three groups (n = 50 per group): (1) protein–energy supplement with S. cerevisiae postbiotic, (2) standard protein–energy supplement, and (3) mineral supplement (control). Gingival health was assessed monthly by oral examination of deciduous incisor teeth, and body weight was recorded to determine average daily gain (ADG). No significant differences in gingivitis frequency were observed among groups (p > 0.05). However, intra-group analysis showed that only the postbiotic-supplemented group maintained stable gingivitis frequency throughout the trial, while the other groups exhibited significant increases (p < 0.001). The postbiotic-supplemented heifers achieved higher ADG (0.300 kg/day) than those receiving the standard protein supplement (0.258 kg/day) and mineral supplement (0.117 kg/day) (p = 0.011). Postbiotic supplementation with S. cerevisiae did not reduce gingivitis occurrence but helped prevent its progression and improved weight performance. These findings indicate that postbiotics may contribute to maintaining oral health and productivity in grazing cattle, representing a promising nutritional strategy for sustainable livestock systems.